2016
DOI: 10.1016/j.ajodo.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Ability of mini-implant–facilitated micro-osteoperforations to accelerate tooth movement in rats

Abstract: Introduction While current techniques for accelerated tooth movement (ATM) often involve invasive surgical procedures, micro-osteoperforations (MOPs) using mini-implants (MI) may facilitate orthodontic tooth movement without raising flaps, reducing surgical risks and increasing patient acceptance. In this study, we evaluated the effectiveness of MI-facilitated MOPs in inducing ATM and investigated potential risks for root resorption. Methods Five MOPs were placed on the left side around the maxillary first m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 41 publications
1
47
2
3
Order By: Relevance
“…As a direct result, they opt for alternative methods such as implants or veneers; with less than optimal outcomes [2]. The increased demand for rapid orthodontic treatment has led to the introduction of several methods, which also reduce potential risks of dental and periodontal complications such as external apical root resorption, high levels of dental caries, and subsequent gingivitis and periodontitis [3][4][5]. Some of the proposed methods are adequate use of brackets, controlling force levels, and relying on less friction bracket systems, photobiomodulation, pharmacological approaches, or low-intensity laser irradiation [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a direct result, they opt for alternative methods such as implants or veneers; with less than optimal outcomes [2]. The increased demand for rapid orthodontic treatment has led to the introduction of several methods, which also reduce potential risks of dental and periodontal complications such as external apical root resorption, high levels of dental caries, and subsequent gingivitis and periodontitis [3][4][5]. Some of the proposed methods are adequate use of brackets, controlling force levels, and relying on less friction bracket systems, photobiomodulation, pharmacological approaches, or low-intensity laser irradiation [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…RAP was first used in the Wilckodontics treatment method and has proven effective in accelerating tooth movement [20]. However, this method has the disadvantage of requiring a corticotomy surgical procedure; involving cuts in the cortical bone, raising the split-thickness flap, and bone decortication [3,20]. Corticotomy techniques have been effective in inducing rapid tooth movement [21].…”
Section: Introductionmentioning
confidence: 99%
“…A new method which uses micro-osteoperforations (MOPs) to stimulate alveolar bone remodeling without the disadvantages of surgery such as the requirement of corticotomies, cuts in cortical bone, raising split-thickness flap, and decorticating the bone has recently been identified [5,12]. Animal studies revealed that micro-osteoperforations significantly stimulate expression of inflammatory markers and increase the number of osteoclasts and bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This technique has clinical benefits including no need for flap reflection, suturing, surgical malleting, or oscillation, which cause patient discomfort. The current study applied this technique with minor surgical modification of the atrophic alveolar ridge model on the assumption that tissue healing and the repair process in the atrophic ridge might elicit tissue responses to OTM different from those that occur in sound alveolar bone.…”
Section: Introductionmentioning
confidence: 99%